"Things I did not know": Retrospectives on a Canadian rural male youth suicide using an instrumental photovoice case study. (November 2017) - Creighton, Genevieve M; Oliffe, John L; Lohan, Maria; Ogrodniczuk, John S; Palm, Emma
In Canada, it is young, rural-based men who are at the greatest risk of suicide. While there is no consensus on the reasons for this, evidence points to contextual social factors including isolation, lack of confidential services, and pressure to uphold restrictive norms of rural masculinity. In this article, we share findings drawn from an instrumental photovoice case study to distil factors contributing to the suicide of a young, Canadian, rural-based man. Integrating photovoice methods and in-depth qualitative, we conducted interviews with seven family members and close friends of the deceased. The interviews and image data were analyzed using constant comparative methods to discern themes related to participants' reflections on and perceptions about rural male suicide. Three inductively derived themes, "Missing the signs, " "Living up to his public image, " and "Down in Rural Canada, " reflect the challenges that survivors and young rural men can experience in attempting to be comply with restrictive dominant ideals of masculinity. We conclude that community-based suicide prevention efforts would benefit from gender-sensitive and place-specific approaches to advancing men's mental health by making tangibly available and affirming an array of masculinities to foster the well-being of young, rural-based men.